A new pupillarial scale insect (Hemiptera: Coccoidea: Eriococcidae) from Angophora in coastal New South Wales, Australia - Gullan, Penny J.; Williams, Douglas J. (Zootaxa, 2016)
A new scale insect, Aolacoccus angophorae gen. nov. and sp. nov. (Eriococcidae), is described from the bark of Angophora (Myrtaceae) growing in the Sydney area of New South Wales, Australia. These insects do not produce honeydew, are not ant-tended and probably feed on cortical parenchyma. The adult female is pupillarial as it is retained within the cuticle of the penultimate (second) instar. The crawlers (mobile first-instar nymphs) emerge via a flap or operculum at the posterior end of the abdomen of the second-instar exuviae. The adult and second-instar females, second-instar male and first-instar nymph, as well as salient features of the apterous adult male, are described and illustrated. The adult female of this new taxon has some morphological similarities to females of the non-pupillarial palm scale Phoenicococcus marlatti Cockerell (Phoenicococcidae), the pupillarial palm scales (Halimococcidae) and some pupillarial genera of armoured scales (Diaspididae), but is related to other Australian Myrtaceae-feeding eriococcids.